PENGARUH SERTIFIKASI GURU TERHADAP KINERJA GURUDI SMA NEGERI 8 KOTA JAMBI - Anggraini, Nurhaliza; Hutabarat, Zuhri Saputra (SJEE (Scientific Journals of Economic Education), 2022)
This study aims to, (1) determine the description of teacher certification in SMA Negeri 8 Jambi City. (2) Knowing the description of teacher performance at SMA Negeri 8 Jambi City (3) Knowing the effect of teacher certification on teacher performance at SMA Negeri 8 Jambi City. This study uses quantitative research using the Simple Regression Test survey method. The population in this study were teachers at SMA Negeri 8 Jambi City with a total of 85 teachers. Collecting data in this study using a questionnaire, and interviews are used to determine the teacher certification variables and teacher performance variables. This data analysis technique used is a simple regression analysis technique using SPSS Version 21 software. The results show that teacher certification at SMA Negeri 8 Jambi City is in the very good category of 86.32% and teacher performance is 85.30%. The existence of the effect of certification on teacher performance at SMA Negeri 8 Jambi City obtained a value of t count = 9.961, meaning that the results of the analysis and discussion of teacher certification (X) have a positive and significant effect on teacher performance (Y) where the regression coefficient is 0.475. Keywords: Teacher Certification and Teacher Performance.